Kabua Ncore Harmoni sosial budaya lokal dalam perspektif Ekonomi Islam di Masyarakat Bima - Rafiudidn, Rafiuddin (Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
This study explores the Kabua Ncore tradition in the Bima community (Mbojo ethnic group) from an Islamic economic perspective. As a form of local wisdom, Kabua Ncore serves not only to resolve social conflicts but also to promote social harmony grounded in justice-based cultural and economic values. Using a phenomenological approach, the research highlights the tradition’s alignment with Islamic economic principles, such as social justice, solidarity, and collective resource management. Practices like Mbolo Rasa, Doho Sara, and Teka Ra Nee illustrate mutual cooperation and assistance. The involvement of religious leaders and socio-religious activities strengthens social harmony and prevents communal conflicts. Economically, Kabua Ncore enhances social capital and promotes equitable resource distribution, reflecting Maqashid Syariah values, particularly in preserving wealth, life, and relationships. The study recommends revitalizing this tradition as a sustainable solution to modern socio-economic challenges in the Bima community